Edukasi Dini Kepedulian Orang Tua Terhadap Pendidikan Anak Untuk Menyelesaikan Program Wajar 9 Tahun Di Kecamatan Tolangohula Gorontalo - Halim K. Malik (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2021)
The results of the Parent Concern for Children's Education Program for Solving 9-YearCompulsory Education, are: First, parental supervision of children's education is verylow, because it is influenced by the perception that the school is just for teaching reading,writing and arithmetic. Second, parents do not provide educational facilities at home tosupport learning acquired in school. Third, high rates of school dropouts due to the valuesembraced by parents who think school is not a guarantee to get a decent job. Fourth, thefactors that influence parents concerns are not responding positively to 9-year compulsoryeducation program, and the interest and motivation of children would come from thefamily itself.